Rēzekne Jewish Cemetery as a Representative Substructure of the “Other” in the Culture of Latgale - Senkāne, Olga (Acta humanitarica academiae Saulensis, 2023)
The aim of this study is to analyze the verbal and non-verbal signs of the Rēzekne Jewish cemetery with the cultural semiotic approach and to find out the hybridization features of the Jewish semiosphere in Latgale. The article describes the Rēzekne Jewish cemetery as a representative substructure of the “other” in the culture of Latgale with special traditions of language and ritual graphics, valuable genealogical material and historical evidence about the fate of local Jews and with a special tomb cult, determined by the ethnically diverse environment.Jews in Latgale have always nurtured and preserved their cultural otherness; this is also characteristic of their traditions of arranging cemeteries. Depending on the cultural and social trends of the relevant era, it is possible to trace changes in the formation of grave inscriptions, graphics and forms. Interrelations with the traditions of the local majority, the Latgalians, show the hybridization of the culture of Jewish cemeteries. In the 20th century, Yiddish is gradually disappearing from grave inscriptions, that is caused by decreasing of the number of its speakers. During the Soviet occupation, the role of the sacred language – Hebrew in grave inscriptions decreased, while the proportion of Russian in the narrative of the inscriptions increased. During the last decade of the 20th century, grave inscriptions are predominant in Russian, which confirms the decline in the number of Hebrew speakers. The symbolic meaning of tomb cult graphics in the second half of the 20th century levels off, and local Jews take over Latgalian traditions of the design of tombstones. The graphic shows the transmission of information to the receivers of the “other” culture, for example, the yellow Star of David is represented instead of the menorah, since the yellow six-pointed star is more recognizable to the local population as a testimony of the Holocaust. A menorah may not cause an association with a Jew, because candles and candlesticks are usual graphic elements of Latgalian tombs. Such a trend in the choice of symbols indicates a unique cultural dialogue and its implementation tools, which are oriented towards the self-presentation of a separate ethnic group, using recognizable stereotypical signs instead of specific cult symbols, the language of local residents instead of their sacred language. They want to be understood and understandable for themselves because the number of people who know the authentic meaning of Hebrew and sacred cult signs in Latgale and Rēzekne is quite small. In any case, communication or cultural dialogue still exists, at least the tomb culture is still capable of transmitting its basic values in the form of stereotypical, well-known signs. In this way, the “other” tends to be noticed and understood.
Keywords: „kita“ latgaliečių kultūroje; semiosfera; žydų kapinės; neverbalinė komunikacija; ritualinė grafika